Implementasi Penegakkan Kode Etik Profesi Dalam Kasus Tindakan Pelanggaran Kode Etik Pada Komisi Pemberantasan Korupsi - Ananda Rafli Haritsah; Kayus Kayowuan Lewoleba (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
The Corruption Eradication Commission (KPK) Code of Ethics is a code of conduct that contains an explanation of the basic principles and values of personal behavior that must be implemented by all KPK employees. This code of ethics aims to ensure that KPK employees carry out their duties with integrity, professionalism and independence, as well as building public trust in the Corruption Eradication Committee as a law enforcement agency that is free from influence from any party. There are so many cases of violations of the professional code of ethics committed by KPK individuals in this era, so it is necessary to have fair and binding legal enforcement and sanctions so that violations of the code of ethics, especially the Corruption Eradication Commission (KPK) which has many pillars as a pillar of legal supremacy in Indonesia, do not lose public trust. The research method that the author uses is normative juridical legal writing in writing this article by carrying out a process to identify legal regulations and principles that contribute to solutions to the problems that will be discussed and faced by the author. Law enforcement in violation of the KPK's professional code of ethics which the KPK As a law enforcement agency in Indonesia, It is important to note that the KPK, as a corruption eradication agency, is expected to have high standards of ethics and integrity.